THE USE OF VUE.JS WITH AN API REST IN SPRING BOOT - Souza, William Gabriel de; Pinto, Giuliano Scombatti (Revista Interface Tecnológica, 2020)
Single page application (SPA) applications are widely used today in the most varied contexts to optimize interactions with users. Therefore, the objective of this article is to present the necessary resources for the development of a single page application for the management of inventories. The front-end was developed by using the progressive JavaScript framework Vue.js. The development of the back-end was carried out by using the Java framework, Spring Boot to develop a Rest API. The methodology used for the development of this work was bibliographic research in books, articles, websites, e-books, among others. It was concluded that Vue.js together with Spring boot allows for an application of great scalability of resources and decoupling among components, in addition to a cleaner organization of the code.
Keywords: JavaScript; Vue.js; Java; Spring; Framework; Single Page Application